United States’s Intervention Through Hollywood Film Industry In Achieving Military Security - rakatama akbar (Mediasi: Journal of International Relations, 2018)
AbstractThis research aims to find out how the intervention of the United States to achieve military security interests. In terms of the achievement of military security interests, the United States generally increases military training, and facilitates military weapons equipment for military troops, by establishing a global security combat position that mobilizes all national powers, preventing the proliferation of weapons of mass destruction, particularly nuclear weapons, facing the global. In this thesis will discuss, to achieve military security United States intervened Hollywood film industry, because the balance of power between hard power and soft power is necessary in maintaining the stability of military security. The researchers used two conceptual frameworks to analyze this research, namely the concept of power, and the concept of foreign policy. This study uses descriptive analysis to explain the issues discussed in this thesis. From this study, it was found that intervention by the United States through the Hollywood film industry to achieve military security in the form of dictating, censoring, and simultaneously changing the script on the film to be produced. The use of Hollywood as a tool to achieve military security interest is appropriate, since United States has a hard power will increase if supported by soft power, therefore the balance of power between the military as hard power, and Hollywood as soft power is necessary to maintain stability military security.Keyword: United States, Hollywood, Power Balance, and Military Security.